Mandelstam and Heraclitus - Kikhney, Liubov (Literatūra, 2020)
The article proves that the ontological poetics of Osip Mandelstam and one of his sources of the concept of the word lie in the doctrine of the Logos of Heraclitus of Ephesus, which is set in the surviving fragments of his treatise On Nature. The author comments on the explicit and hidden references of Mandelstam to Heraclitus and shows the specifics of the functional refraction of Heraclitic allusions in different periods of the Acmeist poet’s work.It is noted that Mandelstam received from Heraclitus the material-being and sensually perceived the integral and hypostatic idea of the Logos as a kind of cosmic law, and at the same time as an ordinary human word, the form of which can nevertheless conceal an analogy with the laws of the world order.Like Heraclitus, Mandelstam assumes that the universe (cosmos) has different stages of formation, controlled by the Logos. According to Heraclitus, the primary basis of the world, its material root is fire. The idea of the changing state of natural substances, their mutual transitions and transformations caused by the “world fire,” which goes back to Heraclitus, permeates a number of the poet’s works written in the era of social upheavals. In the “post-revolutionary” period, Mandelstam develops the idea of the unity of the world and aeonic time, based on Heraclitus. Heraclitic overtones are discerned in a number of Mandelstam’s poems of the 1920s and 30s, including one of his final works – Poems about the Unknown Soldier.In light of the discovered references, Mandelstam, with the sayings of Heraclitus, clarified a number of aesthetic ideas and tropic moves of the poet – for example, the idea of the correlation of how sound envelops speech and its meaning; the motive is the “fluidity” of the world and at the same time its structural unity; the method of the “reversible metaphor of,” marking the identity or paradoxical union of different and sometimes antinomic phenomena.
Keywords: Logos; fire; ontological poetics; “reversible metaphor”; roll calls; allusions; receptions; antithesis; identity